Effect of Probiotic form on Properties of Milk Ice Cream - Pongtrakul, Nongkran; Rodboonrit, Tanutta; Popluechai, Siam; Niamsup, Piyanuch; Deejing, Somkid; Wongputtisin, Pairote (Journal of Food Technology, Siam University, 2018)
Milk ice cream is a promising sweet as an effective probiotic-carrier food into consumer body to contribute a healthiness. This research aimed to produce milk ice cream supplemented with two forms of probiotic Lactobacillus acidophilus TISTR 1338; i.e. free cell and entrapped by Sinlek rice flour and raffinose family oligosaccharides (RFO) from soybean seed. Thus, probiotic and synbiotic ice cream were obtained, respectively. Some properties and the survivability of probiotic in those ice creams were subsequently investigated. The results showed that the color of standard milk ice cream and probiotic ice cream were milky white, while the color of synbiotic ice cream was yellowish. The overrun values of probiotic and synbiotic ice cream were about 65% lower. Moreover, time consumed for the first drop of both formula were 50 and 60% shorter, respectively. On the other hand, time consumed for complete melting was extended approximately 30% in both formula (p<0.05). Meanwhile, pH of all formula were not different (p>0.05). It was interestingly found that L. acidophilus TISTR 1338 in synbiotic powder was able to survive during ice cream processing, which the temperature was below the freezing point of water, approximately 5.82% higher than that of free cell. However, probiotic in both forms could survive efficiently when they were stored at -10oC for 6 weeks.